Quality of care in prevention, detection and management of postpartum hemorrhage in hospitals in Afghanistan: an observational assessment - Nasratullah Ansari; Farzana Maruf; Partamin Manalai; Sheena Currie; Mohammad Samim Soroush; Sher Shah Amin; Ariel Higgins-Steele; Young Mi Kim; Jelle Stekelenburg; Jos van Roosmalen; Hannah Tappis (BMC, 2020)
Abstract Background Hemorrhage is the leading cause of maternal mortality worldwide and accounts for 56% of maternal deaths in Afghanistan. Postpartum hemorrhage (PPH) is commonly caused by uterine atony, genital tract trauma, retained placenta, and coagulation disorders. The purpose of this study is to examine the quality of prevention, detection and management of PPH in both public and private hospitals in Afghanistan in 2016, and compare the quality of care in district hospitals with care in provincial, regional, and specialty hospitals. Methods This study uses a subset of data from the 2016 Afghanistan National Maternal and Newborn Health Quality of Care Assessment. It covers a census of all accessible public hospitals, including 40 district hospitals, 27 provincial hospitals, five regional hospitals, and five specialty hospitals, as well as 10 purposively selected private hospitals. Results All public and private hospitals reported 24 h/7 days a week service provision. Oxytocin was available in 90.0% of district hospitals, 89.2% of provincial, regional and specialty hospitals and all 10 private hospitals; misoprostol was available in 52.5% of district hospitals, 56.8% of provincial, regional and specialty hospitals and in all 10 private hospitals. For prevention of PPH, 73.3% women in district hospitals, 71.2% women at provincial, regional and specialty hospitals and 72.7% women at private hospital received uterotonics. Placenta and membranes were checked for completeness in almost half of women in all hospitals. Manual removal of placenta was performed in 97.8% women with retained placenta. Monitoring blood loss during the immediate postpartum period was performed in 48.4% of women in district hospitals, 36.9% of women in provincial, regional and specialty hospitals, and 43.3% in private hospitals. The most commonly observed cause of PPH was retained placenta followed by genital tract trauma and uterine atony. Conclusion Gaps in performance of skilled birth attendants are substantial across public and private hospitals. Improving and retaining skills of health workers through on-site, continuous capacity development approaches and encouraging a culture of audit, learning and quality improvement may address clinical gaps and improve quality of PPH prevention, detection and management.